(untitled) (Research, Society and Development, 2021)
Breast cancer is currently the cancer that most affects women worldwide, and taking into account that the appearance of this pathology is the sum of several factors such as genetic predisposition, it becomes complex the elaboration of disease prognoses. Thus, it is necessary to seek means based on scientific research that can help in this context. This study aimed to discuss the existing conformity between cellular relations and their meanings in breast cancer. For this, an integrative literature review was carried out in the PubMed database of the productions from the last 10 years. The descriptors used were: "neutrophil lymphocyte ratio", "monocyte lymphocyte ratio", "breast cancer" and "prognosis", which were combined to delimit the search. Six articles were selected at the end of the search steps. Being the years 2018 and 2020 the most prevalent with 33.3% of publications each, followed by the year 2019 and 2021 with 16.6% of publications each. Regarding the country of origin of the studies, 2 articles were conducted in Poland (33.3%), and in each of these countries, being China, Spain, Belgium, and the Republic of Korea, one article was published respectively (16.6%). Evidence showed that patients with higher NLR obtained shorter survival time, on the other hand, patients with higher values of LMR had better prognosis than the other relations. Therefore, it is worth emphasizing the importance of cellular ratios to be investigated in patients with breast cancer in order to optimize the prognosis and, consequently, to seek the best therapeutic methods to raise the survival time of neoplastics.